Vadose zone perspectives in global arsenic research: A review and future opportunities - C. M. vanGenuchten; K. Wang; R. Jakobsen (Vadose Zone Journal, 2024)
Abstract Few contaminants have been linked to more devastating human health and environmental impacts than carcinogenic arsenic (As). Geogenic As contamination of groundwater used as a drinking water source continues to threaten hundreds of millions of lives worldwide, with the As crisis in South and Southeast Asia often called “the largest mass poisoning in history.” In addition, anthropogenic As pollution derived from industrial activities (e.g., mining and smelting processes, wood preservation, and historic pesticide use) has created large sites of intensely contaminated soils and water bodies that urgently require remediation. Because of its profound negative impacts on environmental quality, As has also been the focus of considerable scientific research. In particular, vadose zone research, which aims to understand fluid flow and contaminant transport in variably saturated porous media, has been critical to identify sources of As contamination, predict the fate of As in natural and engineered systems, and help guide regulatory agencies, policymakers, and practitioners to minimize As impacts. In this work, we review several key topics in global As research that have been advanced by vadose zone knowledge. These topics include the release of geogenic As to groundwater, the remediation of anthropogenic As contamination, and the design and operation of As treatment systems. We end this review by highlighting urgent and important knowledge gaps in As research that can benefit from a more rigorous understanding of vadose zone processes.